A digitalização do território paulista: manifestações atuais e tendências que prevalecem - Mónica Arroyo (Confins)
Throughout the 20th century, the state of São Paulo had a significant volume of public and private investments that strengthened the expansion of economic activity and, at the same time, enabled the construction of engineering systems designed to facilitate territorial fluidity. Infrastructures were built for material and immaterial flows, that are being updated in the first decades of the 21st century as the digitalization process advances and new connectivity requirements emerge. This dynamic, while denoting São Paulo's central role in the territorial division of labour on a national scale, also reveals the existence of differentiations within the state. This article aims to outline the general manifestations of the digitalization of the territory and analyze the development of this process in the state of São Paulo.